Versatile rare-earth oxide nanocomposites: enhanced chemo/photothermal/photodynamic anticancer therapy and multimodal imaging. Issue 48 (11th November 2016) - Shen, Tingting; Zhang, Yu; Kirillov, Alexander M.; Hu, Binbin; Shan, Changfu; Liu, Weisheng; Tang, Yu
Abstract : A novel theranostic nanocomposite was assembled by a stepwise modification of rare-earth oxide nanoparticles; both the photothermal and photodynamic therapy effects are enhanced due to the effective light protection of a two-photon sensitized Eu 3+ complex. Abstract : The development of novel nanocomposites that combine multiple imaging and therapeutic strategies has recently attracted considerable attention because of their cumulative and synergistic therapeutic effects. In this study, doxorubicin (DOX)- and indocyanine green (ICG)-loaded Gd2 O3 :Eu 3+ @P(NIPAm- co -MAA)@THA@cRGD nanocomposites {abbreviated as DOX-ICG-TPNPs@cRGD; P(NIPAm- co -MAA): poly[( N -isopropylacrylamide)- co -(methacrylic acid)]; THA: 4, 4-trifluoro-1-(9-pentylcarbazole-3-yl)-1, 3-butanedione; cRGD: cyclic(Arg-Gly-Asp-d -Phe-Lys)} were designed, assembled, fully characterized, and successfully applied in multimodal imaging diagnosis and therapy. The designed nanocomposites display a versatile, multifunctional platform that includes (a) simultaneous targeting with cRGD, (b) multimodal imaging, including two-photon luminescence (TPL), magnetic resonance imaging (MRI), computed tomography (CT), and photothermal imaging (PTI), and (c) stimuli-responsive coordinated drug delivery; this results in a highly efficient synergistic chemo/photothermal/photodynamic anticancer therapy (chemo/PTT/PDT). An important feature of the obtained nanocomposites is the enhancement of both the PTT and PDT effects of ICG due to the effective light protection of a two-photon sensitized Eu 3+ complex. This integrated strategy shows an excellent synergistic inhibition of tumor growth triggered by NIR laser irradiation, as confirmed by both in vitro and in vivo tests. The present study emphasizes the influence and interaction of every component in the nanocomposites and demonstrates that the systematic design of nanocarriers can lead to an assembly of smart nanomaterials with enhanced antitumor efficacy.